Deficiency in flavonoid biosynthesis genes CHS, CHI, and CHIL alters rice flavonoid and lignin profiles. Issue 4 (28th December 2021) - Lam, Pui Ying; Wang, Lanxiang; Lui, Andy C W; Liu, Hongjia; Takeda-Kimura, Yuri; Chen, Mo-Xian; Zhu, Fu-Yuan; Zhang, Jianhua; Umezawa, Toshiaki; Tobimatsu, Yuki; Lo, Clive
Abstract: Lignin is a complex phenylpropanoid polymer deposited in the secondary cell walls of vascular plants. Unlike most gymnosperm and eudicot lignins that are generated via the polymerization of monolignols, grass lignins additionally incorporate the flavonoid tricin as a natural lignin monomer. The biosynthesis and functions of tricin-integrated lignin (tricin-lignin) in grass cell walls and its effects on the utility of grass biomass remain largely unknown. We herein report a comparative analysis of rice ( Oryza sativa ) mutants deficient in the early flavonoid biosynthetic genes encoding CHALCONE SYNTHASE (CHS), CHALCONE ISOMERASE (CHI), and CHI-LIKE (CHIL), with an emphasis on the analyses of disrupted tricin-lignin formation and the concurrent changes in lignin profiles and cell wall digestibility. All examined CHS-, CHI -, and CHIL -deficient rice mutants were largely depleted of extractable flavones, including tricin, and nearly devoid of tricin-lignin in the cell walls, supporting the crucial roles of CHS and CHI as committed enzymes and CHIL as a noncatalytic enhancer in the conserved biosynthetic pathway leading to flavone and tricin-lignin formation. In-depth cell wall structural analyses further indicated that lignin content and composition, including the monolignol-derived units, were differentially altered in the mutants. However, regardless of the extent of the lignin alterations, cell wall saccharification efficiencies of all tested rice mutants were similar to that of the wild-type controls. Together with earlier studies on other tricin-depleted grass mutant and transgenic plants, our results reflect the complexity in the metabolic consequences of tricin pathway perturbations and the relationships between lignin profiles and cell wall properties. Abstract : Mutating early flavonoid biosynthetic genes differentially affects the structure and content of tricin-incorporated lignin in rice cell walls. P.Y.L., L.W., A.C.W.L., H.L., Y.T.K., M.X.C., F.Y.Z., and Y.T. performed experiments. P.Y.L., L.W., T.U., J.Z., Y.T., and C.L. conceived research and analyzed data. P.Y.L., Y.T., and C.L. wrote the manuscript with help from all the others.